1979
DOI: 10.1159/000198330
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Somatostatin on Normal and Gastric-Stimulated Cell Proliferation in the Gastric and Intestinal Mucosae of the Rat

Abstract: The effects of an 8-hour infusion of somatostatin, saline, gastrin or a mixture of gastrin + somatostatin on DNA synthesis and mitotic activity of gastrointestinal progenitor cells were explored in conscious rats, using in vivo labeling with 3H-thymidine and radioautography. Infusion of somatostatin (day or night) was shown to transiently reduce nuclear uptake of 3H-thymidine and cell division in both fundic and antral progenitor cells. Cell DNA synthesis in the gastrin + somatostatin-sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1
1

Year Published

1985
1985
2000
2000

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(40 citation statements)
references
References 18 publications
(24 reference statements)
2
36
1
1
Order By: Relevance
“…Injections of gastrin did not significantly affect cell proliferation of small intestinal epithelial cells, but stimulated cell proliferation in the colon of rats (Fatemi et al 1984). Somatostatin, on the other hand, had an inhibitory effect on DNA synthesis of gastrointestinal stem cells in vivo in rats (Lehy et al 1979) and rat intestinal epithelial cells in vitro (Bjork et al 1993). Somatostatin and its analogs have been shown to induce enterocyte apoptosis and impair intestinal regeneration after resection in rabbits (Thompson 1998.…”
Section: Physiological Mediators Of Intestinal Apoptosismentioning
confidence: 97%
“…Injections of gastrin did not significantly affect cell proliferation of small intestinal epithelial cells, but stimulated cell proliferation in the colon of rats (Fatemi et al 1984). Somatostatin, on the other hand, had an inhibitory effect on DNA synthesis of gastrointestinal stem cells in vivo in rats (Lehy et al 1979) and rat intestinal epithelial cells in vitro (Bjork et al 1993). Somatostatin and its analogs have been shown to induce enterocyte apoptosis and impair intestinal regeneration after resection in rabbits (Thompson 1998.…”
Section: Physiological Mediators Of Intestinal Apoptosismentioning
confidence: 97%
“…The native peptide is widely distributed in the body and, amongst its many inhibitory actions, has a putative role as an anti-proliferative agent in both normal (Lehy et al, 1979) and malignant tissue. The mechanisms involved in this anti-proliferative action have not, as yet, been confirmed.…”
mentioning
confidence: 99%
“…Later, a direct antiproliferative effect of octreotide on the gastric mucosa (as documented for somatostatin-14 in the rat (27)), as well as a diminished trophic effect of gastrin may become effective. This is in keeping with the reduction in the volume and density of endocrine cells (mostly ECL cells) in the body mucosa (by 43 and 21% respectively) found in hypergastrinemic patients after 6 months of octreotide therapy (37).…”
Section: Intragastric Aciditymentioning
confidence: 96%
“…We have previously demonstrated that this inhibition of gastrin secretion persists during long-term treatment (several years) in acromegalic patients (18). As gastrin is an important trophic factor in the gastric mucosa (27), long-term disturbance of its physiological secretion could adversely affect mucosal morphology.…”
Section: European Journal Of Endocrinology (1998) 139mentioning
confidence: 97%
See 1 more Smart Citation